What brings people to government urban primary care facilities? A community-based study from Delhi, India - Nitish Virmani; Ishaan Mittal; Chandrakant Lahariya (Wolters Kluwer Medknow Publications, 2022)
Introduction: Mohalla or Community Clinics of Delhi, India, provides free primary care services to the general population, with special focus on the underserved and marginalized. This study was conducted to analyze the perception and experience of target beneficiaries and to understand and document the determinants of people visiting these clinics. Material and Methods: A community-based study was conducted from October 2019 to April 2020. A semi-structured questionnaire was used for data collection. Correlation and comparative analysis were used. Thirty-seven Mohalla Clinics and their catchment areas were visited. A total of 391 respondents (including 35 health staff and 356 community members) were included. Results: Proximity of clinics, waiting times, age, perceived quality of treatment, and cleanliness at facilities were the factors that influenced the usage of clinics. Lack of first-aid facilities and long waiting time (at a few facilities) were identified challenges. There is a need for wider publicity and awareness about the clinics and regular analysis of data to determine an appropriate mid-course action to further increase utilization. Conclusion: Community Clinics of Delhi, India, have brought people back to government primary healthcare (PHC) facilities. The popularity of these clinics has encouraged a number of Indian states to set up similar facilities. The factors behind their success need to be studied in detail to derive lessons for making urban PHC accessible in other low- and middle-income countries.